Beach response to high energy wave climate: a case study in the portuguese west coast - Trindade, J. (2020)
Portugal’s western coast is a wave-dominated rocky coast with a semidiurnal mesotidal regime. The wave climate is highly conditioned by the Atlantic Ocean’s atmospheric circulation, which results in a seasonalchange in wave patterns. Storms are frequent during winter and can reach 10-m wave heights with a 5-year recurrence period. Four profile monitoring campaigns were carried out in December 2005, January and May 2006 using a GPS and a total station to evaluate the response of three different beach systems to high wave climate events, comparing pre-storm wave, morphology and sediment characteristics with the modifications induced in the system after the storm event. A series of 64 beach profiles is analysed in terms of sediment textural properties, volume, slope, surf similarity index and dimensionless fall velocity parameters’ variability. Each beach system’s modal and limit morphological behaviours are established according to Wright and Short’s morphodynamic model.